IMPACT OF COVID-19 ON PUBLIC SERVICE SUPPLY (IN THE CONTEXT OF LOCAL SELF-GOVERNMENT) (Globalization and Business, 2023)
The last two years in the history of mankind can be characterized as the beginning of a nation of difficulties caused by the spread of the coronavirus pandemic. The pandemic has broken all borders (political, legal, state), and overcoming the transboundary global crisis has necessitated the participation of all levels of government and the private sector.  The pandemic, along with human health, attacks the socio-economic sphere and poses obvious threats of economic depression, rising unemployment and poverty, limited social contacts, and many other negative events. This threat affects the state and municipal management and, consequently, the public services provided by them. Unfortunately, unlike trade and education, these types of services are largely impossible to digitize.  In the current situation, the attention of citizens and business representatives is drawn to the actions of the state, as its activities and management skills have acquired much more function. Meeting the needs of citizens in a pandemic requires the use of approaches based on new technologies, new forms of interaction, and innovative methods of work.  The economic sustainability of public administration occupies an important place in public policy as a determinant of public sector modernization, support, optimization of functioning, and improvement of public services. This acquired a special load during the crisis caused by the corona pandemic.  The ongoing coronavirus pandemic dictates that it is necessary to develop new approaches to state intervention and public service delivery systems in all areas of public life in times of crisis in order to respond optimally to the needs of citizens.